PHYSIOLOGICAL POTENTIAL AND WATER AVAILABILITY ON SEED GERMINATION AND EARLY GROWTH OF MAIZE - VAZQUEZ, G. H.; SILVA, T. F. DA; ASSIS, A. V. DE (Revista Brasileira de Engenharia de Biossistemas, 2013)
The purpose of this work was to study the effects of seed physiological potential and soil water availability in the germination process and early development of maize. The experiment was conducted in a greenhouse at UNICASTELO in Fernandópolis/SP with seeds of hybrid 8480. The experimental design used was the completely randomized in factorial arrangement 6 x 4, i.e. six lots with germination of 91, 93.5, 94, 95, 97 and 97.5% and four levels of moisture in the soil by irrigation (100%, 75%, 50% and 25% of the available water capacity of the soil), with four replicates of 50 seeds. The data obtained allowed to conclude that: the irrigation level of 75% of field capacity provides the largest percentages and speed of emergence; the higher is the physiological potential of seeds, the higher the speed of emergence, seedling height and dry matter weight, with no interference on the emergence percentage and finally, the higher the water availability in the soil, the greater the height and weight of dry matter in maize seedlings.